Cardiac Sympathetic Hyperactivity in Patients with Chronic Obstructive Pulmonary Disease and Obstructive Sleep Apnea. (1st November 2016) - Taranto-Montemurro, Luigi; Messineo, Ludovico; Perger, Elisa; Salameh, Maroon; Pini, Laura; Corda, Luciano; Ferliga, Mauro; Tantucci, Claudio
ABSTRACT: Obstructive sleep apnea (OSA) and chronic obstructive pulmonary disease (COPD) coexist in 0.5–1% of the general population. Both OSA and COPD are associated with increased sympathetic nervous activity, and patients affected by both disorders have higher risk for increased morbidity and mortality as compared with patients with COPD or OSA alone. We tested the hypothesis that patients with COPD and OSA (Overlap syndrome) have higher sympathetic and lower parasympathetic modulation of heart rate variability (HRV) in comparison with patients suffering from COPD or OSA alone. HRV indices in the frequency domain were evaluated from daytime electrocardiographic recordings in 14 patients with both severe OSA (apnea–hypopnea index ≥ 30) and mild-to-moderate COPD and compared with those with OSA ( n = 24) or COPD ( n = 16) alone. We found that, in the Overlap syndrome group, high-frequency (HF, 0.4–0.15 Hz) power was significantly lower (0.18 nu vs 0.34 nu in OSA and 0.44 nu in COPD patients, p < 0.01) and low-frequency (LF, 0.15–0.05 Hz) power was significantly greater (0.82 nu vs 0.66 nu in OSA and 0.57 nu in COPD patients, p < 0.01) compared with COPD and OSA groups. Patients with both OSA and COPD had higher LF/HF ratio as compared with patients in OSA and COPD groups (4.5 [5.9] vs 1.9 [2.6] and 1.3 [1.3], respectively, p < 0.01). For the Overlap syndrome group, there was a significant direct relationship between LF/HF ratio and residual volume ( r 2 = 0.62, p = 0.007). These findings show that patients with both OSA and COPD have higher sympathetic modulation of heart rate compared with those with OSA or COPD alone. Furthermore, the findings provide a potential mechanism for the increased morbidity and mortality reported in patients suffering from both disorders, suggesting new therapeutic perspectives in Overlap syndrome.